Ecological momentary assessment of interpersonal theory of suicide constructs in people experiencing psychotic symptoms. (August 2021) - Parrish, Emma M.; Chalker, Samantha A.; Cano, Mayra; Moore, Raeanne C.; Pinkham, Amy E.; Harvey, Philip D.; Joiner, Thomas; Lieberman, Amy; Granholm, Eric; Depp, Colin A.
Abstract: Background: People with psychotic disorders are at an increased risk of suicide, but there is little understanding of suicidal ideation (SI) in this population. The Interpersonal Psychological Theory of Suicide posits that perceived burdensomeness (PB) and thwarted belonginess (TB) contribute to SI. To our knowledge there are no studies using ecological momentary assessment (EMA) to assess these interpersonal risk factors in a sample of individuals with psychotic disorders. This study investigated the validity and variability of PB and TB, and whether SI, EMA-measured psychotic symptoms, mood, and social context relate to PB and TB. Method: Ninety-six participants with a psychotic disorder, including mood disorders with psychosis completed in-lab assessments of current SI, and then EMA surveys on a smartphone 3×/day for 10 days, answering questions about burdensomeness, belongingness, symptoms (i.e., hearing voices, experiencing suspiciousness), mood (i.e., happy, sad), and social context. Results: Burdensomeness varied within-participants less than belongingness ( t (95) = -3.74, p =< .001). Participants with SI had higher mean burdensomeness ratings ( t (94) = -2.70, p < .01) and lower mean belongingness ratings ( t (94) = 3.68, p < .001) than did participants without SI. Being with others, greater psychotic experiences, less happiness, and greater sadness related to greater burdensomeness. SI status, being alone, greater psychotic experiences, less happiness, and greater sadness related to less belongingness. Conclusions: This study examined the real-time influences of SI and psychotic symptoms on burdensomeness and belongingness. Hearing voices, suspiciousness, mood, and SI are related to interpersonal suicide-related risk factors. In this sample, social context had a differential effect on burdensomeness and belongingness.